Absolutely fabulous [videorecording (DVD)] : the movie - Moss, Kate; Saunders, Jennifer; Saunders, Jennifer; Lumley, Joanna; Horrocks, Jane, 1964- (20th Century Fox Home Entertainment, 2016)
After grabbing the attention of both the media and police for accidentally knocking Kate Moss into a River, Edina and Patsy hide out in the south of France to escape the paparazzi frenzy.